Evaluation of the positive impacts of e-customs implementations on foreign trade by fuzzy AHP method - Danacı, Tugce (My University, 2023)
This study aims to evaluate the positive impacts of e-customs implementations on international trade and rank these impacts hierarchically according to their importance weights. For this purpose, Fuzzy Analytical Hierarchy Process (AHP) method was applied to analyze the importance weights of each impact. Data were collected from the experts by conducting a survey prepared following the study's research method. Questionnaire forms were structured within the conceptual model framework created in line with the literature review and expert decisions. Questionnaires were sent via e-mail to the experts and fully completed seven of them were included in the analysis. Results of the study demonstrate that the Time criterion has the highest impact on e-customs implementations among the main criteria. Besides, the first three important impacts of e-customs implementations among the subcriteria are ease of transactions, reduced bureaucracy, and faster transactions. The findings obtained from this study are supposed to contribute to the studies concerning e-customs applications.
Keywords: Bilgi; Belge Yönetimi; İşletme; İktisat